Attempt to Optimize the Role of Peer Support Group (PSG) in Increasing the Quality-of-Life Persons Living With HIV/AIDS (PLWHA) Through the Revitalization of Peer Support Activities Program in Pati Regency - Irnawati, Yuli (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
It is well-known that People Living With HIV/AIDS (PLWHA) are denied and avoided by their own families. This is a very heavy social burden that must be borne by PLWHA. Therefore, the role of Peer Support Groups (PSG) as community empowerment is very important to improve the living quality of PLWHA. In this study, community service activities were conducted to optimize the role of PSG in improving the living quality of PLWHA in Pati Regency. Currently, Pati is the fourth highest city with PLWHA in Central Java, Indonesia. The community service utilized guidance participation, which prioritizes the involvement of the community in the activities. The implementation involved analytical methods for problem-solving and completion of the study. Two meetings were held at the Voluntary Counselling and Testing (VCT) Clinic of Soewondo Pati Hospital. In average, one activity was attended by 5-8 participants. They are the volunteer members from PSG Rumah Matahari. The meetings focused on brainstorming sessions and on providing counselling about the Prevention of Mother to Child Transmission (PMTCT) program, which aimed to enhance knowledge about PMTCT among PSG Rumah Matahari volunteers, especially in assisting pregnant women with PLWHA. The results show that the community service activities successfully highlighted the importance of PSG in improving the quality of life for PLWHA. The PMTCT program was well understood by the PSG Rumah Matahari volunteers, indicating the effectiveness of the training.